Strategi Public Relations dalam Membangun Citra dalam Membangun Citra Organisasi: (Studi Deskriptif pada Lembaga Dakwah Islam Indonesia (LDII) - ARIFAH, ARIFAH (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2022)
Lembaga Dakwah Islam Indonesia (LDII) requires a positive image to be more accepted and believed by the people of Indonesia, especially adherents of Islam, due to the stigmatization of heresy inherent in LDII. With a positive image of the community do not have to worry anymore about the teachings of Islam spread by LDII so it can be accepted by all Indonesian people as other Islam community/ mass organizations. Image of LDII has not been positive because there are still negative news on the internet. Therefore, to form a positive image of LDII, public relations need the public relations strategy. The purpose of this study is to know and describe the public relations strategy used by public relations in building a positive image. This study uses image theory to find out the image of LDII, public relations theory and public relations strategy in building the image of the organization. The methodology of this research is descriptive analysis and presentation of data done with qualitative. The results of this research known that the public relations strategy used public relations of LDII in shaping a positive image is with seven public relations strategies namely publication; Event; Creating news; Community involvement; Inform or images; Lobbying or negotiation; As well as social responsibility. All of these strategies succeeded in making LDII's image positive and LDII has been accepted by the people of Indonesia.